: Clima social escolar, desde la percepción de estudiantes y profesores del séptimo año de educación básica de la escuela fiscal mixta urbana Marcos Mero López de la parroquia Leonidas Plaza, cantón Sucre y centro de educación básica rural “Gran Colombia” de la parroquia Charapotó, cantón Sucre, periodo lectivo 2011-2012 - Martinez Cedeño, Elvia Beatriz (2013)
In these days, it’s important to know all the teaching management ability and school environment concepts, because they cause a huge impact to all the involved people. This investigation searches the perception of these concepts from the students, seventh grade’s teachers of the “Marcos Mero López”, an urban school located in Bahía de Caráquez, and “Gran Colombia”, a rural school, located in Charapotó, Manabí. Four Moost and Tricket questionnaires were applied to have direct information with descriptive, inductive, deductive, statistical and hermeneutic methods, during the scholar year 2011-2012. In this manner we could obtain some descriptions of the better strategies to improve the teaching management ability and the school environment; with rules and cooperative work and in this way the students could find their intellectual capacity, skills, so the teacher could be motivated to update their knowledge. To overcome the weakness, we design a new proposal “The cooperative work as an effective interactive tool in the classroom to improve interpersonal relationship and capacity to the student, in the school, during the scholar year 2014-2015”.